Improving lithium-sulfur battery performance using a polysaccharide binder derived from red algae - Dóra Zalka; Alen Vizintin; Alexey Maximenko; Zoltán Pászti; Zoltán Dankházi; Kristóf Hegedüs; Lakshmi Shiva Shankar; Róbert Kun; Karel Saksl; Andrea Straková Fedorková; Pál Jóvári (Communications Materials)
Abstract Li-S batteries are a promising energy storage technology due to their high theoretical capacity, but they suffer from issues such as poor cycle stability and capacity loss over time. Here, we investigate the impact of carrageenan, a polysaccharide binder derived from red algae, on the performance of Li-S batteries. Electrode slurries are prepared without the toxic solvent N-methyl-2-pyrrolidone, using only water as a solvent and dispersant, making the process potentially scalable and cost-effective. With the optimal amount of carrageenan, we observe a capacity retention of 69.1% at 4 C after 1000 charge-discharge cycles. Carrageenan-based electrodes deliver 30% higher capacity than those made with the industry-standard polyvinylidene fluoride binder. X-ray photoelectron spectroscopy analysis confirms the chemical binding of carrageenan to the sulfur active material, and transmission X-ray absorption spectroscopy reveals that carrageenan effectively traps shorter-chain lithium polysulfides, improving the overall battery performance.